Editorial - Manna, Sanjib Kumar (Journal of the Inland Fisheries Society of India, 2021)
It gives me immense pleasure to share that with continued regularity and standard of publishing the NASS rating of Journal of the Inland Fisheries Society of India has recently been enhanced from 4.54 to 5.71. I am also happy to announce that IFSI has decided to publish the Journal on quarterly basis, i.e., four issues per year to cater to the need of the scientific community and support fisheries research. I profoundly thank the scientific community for their overwhelming support in the form of research paper and other contributions, despite the global public health emergency of COVID-19. In addition to regular Research papers and Short communications the Journal now publishes Review, Letter to the Editor and Opinion letter in the field of inland fisheries.